БЕСКОНТАКТНЫЙ АСИНХРОНИЗИРОВАННЫЙ ТУРБОГЕНЕРАТОР С ВРАЩАЮЩИМСЯ ПРЕОБРАЗОВАТЕЛЕМ ЧАСТОТЫ В РЕЖИМАХ ГЛУБОКОГО ПОТРЕБЛЕНИЯ И ВЫДАЧИ РЕАКТИВНОЙ МОЩНОСТИ - Галиновский, А.М.; Бобер, В.А.; Дубчак, Е.М. (Інститут електродинаміки НАН України, Київ, 2015)
The analysis of brushless asynchronized turbine generator with the multiphase rotating direct frequency converter with natural commutation and modulated input voltage was made. The purpose of the work is to develop recommendations for the choice of covering asynchronized turbogenerator contactless modes of issuance and deep reactive power consumption when the active power from zero to nominal. In the case of the issuance of the generator reactive power to the network frequency converter provides high quality generator excitation current with changes in the slip from zero to the nominal value. In the case of generator reactive power consumption of network asynchronous rotor speed changes the direction of the flow of reactive power through the circuit winding of the generator. The angle load of converter reaches 60 electrical degrees or more, this can lead to malfunction of the converter. In order to maintain efficiency of the converter at different modes of operation of the generator, as well as fore uniform heating the exciting windings when reactive power generates to network it was recommended to work with synchronous speed in the mode of consumption and asynchronous speed in the mode of issue of reactive power. References 8, table 1, figures 5.